High Spatial Resolution Time-of-Flight Secondary Ion Mass Spectrometry for the Masses: A Novel Orthogonal ToF FIB-SIMS Instrument with In Situ AFM. (18th October 2011) - Whitby, James A.; Östlund, Fredrik; Horvath, Peter; Gabureac, Mihai; Riesterer, Jessica L.; Utke, Ivo; Hohl, Markus; Sedláček, Libor; Jiruše, Jaroslav; Friedli, Vinzenz; Bechelany, Mikhael; Michler, Johann
Abstract : We describe the design and performance of an orthogonal time-of-flight (TOF) secondary ion mass spectrometer that can be retrofitted to existing focused ion beam (FIB) instruments. In particular, a simple interface has been developed for FIB/SEM instruments from the manufacturer Tescan. Orthogonal extraction to the mass analyser obviates the need to pulse the primary ion beam and does not require the use of monoisotopic gallium to preserve mass resolution. The high-duty cycle and reasonable collection efficiency of the new instrument combined with the high spatial resolution of a gallium liquid metal ion source allow chemical observation of features smaller than 50 nm. We have also demonstrated the integration of a scanning probe microscope (SPM) operated as an atomic force microscope (AFM) within the FIB/SEM-SIMS chamber. This provides roughness information, and will also allow true three dimensional chemical images to be reconstructed from SIMS measurements.